A bibliometric analysis of research articles using Q methodology in education in Turkey - YILMAZ VİRLAN, AYŞE (My University, 2022)
In almost every field of education, extensive literature searches are conducted to examine, analyze or explain the results obtained from the studies, trends and approaches that underlie them. This study, too, aims to provide an overview of the research articles made in the field of education in Turkey and using the Q-methodology in the research design, and to examine these studies through bibliometric analysis. For this purpose, research articles published in journals indexed by Scopus, Dergipark, Yöktez and TR Index were examined and a total of 194 articles were reached. After the inclusion criteria were applied, bibliometric analysis was carried out and the articles were examined in terms of year, journal, number of citations, keywords and author. According to the results, it was revealed that only 20 research articles were conducted in the field of education in Turkey, and that these studies were quite limited when compared to other basic sciences.
Keywords: Sosyal ve Beşeri Bilimler; Eğitim; Eğitim Bilimleri; Social Sciences and Humanities; Education; Educational Sciences; Sosyal Bilimler (SOC); Sosyal Bilimler Genel; EĞİTİM VE EĞİTİM ARAŞTIRMASI; Social Sciences (SOC); SOCIAL SCIENCES, GENERAL; EDUCATION & EDUCATIONAL RESEARCH; Sosyal Bilimler ve Beşeri Bilimler; Social Sciences & Humanities